Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) = (x+3).(x-3)^2-(x-3)(x+3)^2
=(x^2-9)(x-3)-(x^2-9)(x+3)
=(x^2-9)(x-3-x-3)
=-6(x^2-9)
các câu còn lại tương tự
\(a,\left(x+3\right)\left(x^2-3x+9\right)-\left(x-3\right)\left(x^2+3x+9\right)\)
\(=x^3+3-\left(x^3-3\right)\)
\(=x^3+3-x^3+3\)
\(=6\)
\(b,\left(x-5\right)\left(x^2+5x+25\right)-\left(x+5\right)\left(x^2-5x+25\right)\)
\(=x^3-5^3-x^3-5^3\)
\(=-125-125\)
\(=-250\)
Ta có: \(\dfrac{x^2-x}{x+3}-\dfrac{x^2}{x-3}=\dfrac{7x^2-3x}{9-x^2}\)
\(\Leftrightarrow\left(x^2-x\right)\left(x-3\right)-x^2\left(x+3\right)=3x-7x^2\)
\(\Leftrightarrow x^3-3x^2-x^2+3x-x^3-3x^2-3x+7x^2=0\)
\(\Leftrightarrow0x=0\)(luôn đúng)
\(\dfrac{x^2-x}{x+3}-\dfrac{x^2}{x-3}=\dfrac{7x^2-3x}{9-x^2}\\ \Leftrightarrow\dfrac{x^2-x}{x+3}-\dfrac{x^2}{x-3}=-\dfrac{7x^2-3x}{\left(x-3\right)\left(x+3\right)}\\ đkxđ:\left\{{}\begin{matrix}x-3\ne0\\x+3\ne0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x\ne3\\x\ne-3\end{matrix}\right.\\ \Leftrightarrow\dfrac{\left(x^2-x\right)\left(x-3\right)}{\left(x+3\right)\left(x-3\right)}-\dfrac{x^2\left(x+3\right)}{\left(x-3\right)\left(x+3\right)}+\dfrac{7x^2-3x}{\left(x-3\right)\left(x+3\right)}=0\\ \Leftrightarrow\dfrac{x^3-3x^2-x^2+3x-x^3-3x^2+7x^2-3x}{\left(x-3\right)\left(x+3\right)}=0\\ \Leftrightarrow\dfrac{0}{\left(x-3\right)\left(x+3\right)}=0\\ \Rightarrow0=0\left(luon.dung\right)\)
\(\frac{x^2-x}{x+3}-\frac{x^2}{x-3}=\frac{7x^2-3x^2}{9-x^2}\) ĐKXĐ : \(x\ne\pm3\)
\(\Leftrightarrow\frac{\left(x^2-x\right)\left(x-3\right)}{\left(x+3\right)\left(x-3\right)}-\frac{x^2\left(x+3\right)}{\left(x+3\right)\left(x-3\right)}=\frac{3x^2-7x^2}{\left(x+3\right)\left(x-3\right)}\)
\(\Leftrightarrow x^3-3x^2-x^2+3x-x^3-3x^2=3x^2-7x^2\)
\(\Leftrightarrow\left(x^3-x^3\right)+\left(-3x^2-x^2-3x^2-3x^2+7x^2\right)-3x=0\)
\(\Leftrightarrow-3x^2-3x=0\)
\(\Leftrightarrow-3x\left(x+1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}-3x=0\\x+1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\x=-1\end{cases}}}\)
KL : nghiệm của PT là : \(S=\left\{0;-1\right\}\)
\(\frac{x-4}{x-1}+\frac{x+4}{x+1}=2\) DKXĐ : \(x\ne\pm1\)
\(\Leftrightarrow\frac{\left(x-4\right)\left(x+1\right)}{\left(x+1\right)\left(x-1\right)}+\frac{\left(x+4\right)\left(x-1\right)}{\left(x+1\right)\left(x-1\right)}=2\)
\(\Leftrightarrow x^2+x-4x-4+x^2-x+4x-4=2\)
\(\Leftrightarrow\left(x^2+x^2\right)\left(x-4x-x+4x\right)+\left(-4-4\right)=2\)
\(\Leftrightarrow2x^2-8=2\)
\(\Leftrightarrow2x^2=10\)
.....
ĐK: ` x \ne \pm 3`
`(x^2-x)/(x+3)-(x^2)/(x-3)=(7x^2-3x)/(9-x^2)`
`<=> (x^2-x)(x-3)-x^2 (x+3) = -(7x^2-3x)`
`<=> −7x^2+3x=-7x^2+3x`
`<=> 0x=0 forall x`
Vậy `S=RR \\ {+-3}`.